Eksistensi Media Cetak di Era Digital: Studi Kasus pada Media Harian Bhirawa - Irfani, Ana Nahdiah; Ruskamila, Alina; Prayogo, Moh. Dey (Universitas Pahlawan Tuanku Tambusai, 2025)
The digitalization era poses significant challenges to print media survival, including Bhirawa Daily. This qualitative case study explores Bhirawa Daily's survival strategies through interviews with editorial teams and digital documentation analysis using Miles and Huberman's interactive method. Results reveal a successful dual-platform strategy where Bhirawa maintains print publication while developing digital platforms including websites, Instagram, Facebook, and YouTube. A unique approach involves student interns managing creative digital content. Key challenges include declining advertising revenue, shifting consumer preferences, and operational cost imbalances. Despite obstacles like publication speed differences and stagnant print readership, Bhirawa overcame these through accelerated editorial processes and digital expansion. Digital platforms create new opportunities through social media integration and innovation. The study concludes that print media can survive the digital era through appropriate adaptation strategies, leveraging young talent and maintaining credibility as competitive advantages.